SYNTACTIC ANALYSIS ON POEM “LOVE ONE ANOTHER” by KAHLIL GIBRAN - Supri, Ida Zuraida; Nugraha, Ihsan; Ndun, Kevin Indira Putra; Deviani, Mira; Arnetta, Putri Wafaa; Putri, Rizka Amalia Gumilar (CENTRAL ASIA AND THE CAUCASUS, 2022)
This research aims to identify the types of sentences and to identify the functions of sentences found in Love One Another Poem. The researcher used theories about syntax from [1]theory and [2] theory to identify the types of sentences and the functions of sentences. The source of the data is taken from a poem written by Kahlil Gibran and titled Love One Another. The method used in this research is the qualitative analysis method proposed by [3] All the data could not be used in mathematical sequences. This method includes several steps, such as collecting, identifying, analyzing, examining and drawing conclusions. Syntax Tree Editor, an application language program, is employed to support the data analysis. The results show that there are two types of sentences used in the poem Love One Another; they are three simple sentences (30%) and seven compound sentences (70%). The functions of sentences are six imperative sentences (60%) and four exclamatory sentences (40%). The imperative function is dominant.